Penggunaan Media Pembelajaran Video Animasi pada Materi Sistem Peredaraan Darah di SMP - Gulo, Denika; Lahagu, Analisi; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The inability of the learning process to reach a conducive level is due to the lack of attractiveness of the learning media used today, which has not been able to arouse students' interest optimally. This happens due to the lack of variety in the use of learning media. The research method used is a qualitative descriptive method. The subject in the study is class VII students, while the object is the implementation of animated videos on the blood circulatory system material. The data collection techniques used include observation. The data analysis of this study was carried out qualitatively with the stages of data reduction, data presentation, and conclusion drawn. The result of this research is that the learning media in the form of animated videos that have been made has met the standards of content, design, and use of media in accordance with the set. This success is due to the fit between the material presented in the animated video and the basic skills, indicators, and learning objectives that have been set. In addition, the animations used are adjusted to the characteristics of the students. It is hoped that the compatibility between these indicators and learning objectives can help students understand the learning material better. Therefore, this learning medium is considered effective in supporting the learning process